The Evaluation of Development of Badminton Clubs Achievements in Cirebon Regency (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
From year to year, the badminton club's achievements in Cirebon Regency have not increased. They have not been able to excel at provincial and national championships. This study aims to evaluate the development of club management, coach, athlete, training, competition, infrastructure, and funding for badminton clubs in Cirebon Regency. The research method is the Countenance Stake evaluation research. Data collection techniques are observation, interviews, and documentation. Data analysis are data reduction methods, data presentation and drawing conclusions. The results of this study are the club management does not have AD/ART of the club and there are multiple positions, the coach is constrained in competency development, there is no standardization in the acceptance of athletes, no standardized training program, the competition agenda for some clubs has been set, the infrastructure for some clubs are already PBSI standard, it does not have a coaching budget planning. The conclusion of this research is that the club management development is not appropriate, the coach development is not appropriate, the athlete development is not appropriate, the training development is not appropriate, the competition development of some of the clubs is appropriate, the infrastructure of some of the clubs is appropriate, the funding is not appropriate.